Ascaris infection, a rare cause of necrotizing pancreatitis in a child - Yadav, Aditya Prakash; Karki, Rishi Kumar; Rai, Binod Kumar (Journal of Chitwan Medical College, 2020)
Necrotizing pancreatitis is a very rare in children and is associated with high morbidity & mortality rates. We report a case of 5yr old boy who presented with upper abdominal pain, vomiting and non-passage of stool for 1day. After resuscitation and investigating the child, a provisional diagnosis of biliary ascariasis (BA) with acute pancreatitis was made. The child developed peritonitis after 2 days of admission and exploratory laparotomy was planned. An intraoperative diagnosis of necrotizing pancreatitis was made and the child was successfully managed.